Islamization and the Ethnographic Construction of Muslim Identity: The Networks of Ulama and Syncretism in Indonesia and Malaysia - Ananda Alisya Qothrunnada Munawaroh; Thobib Al-Asyhar; Mohammad Izdiyan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This article examines the process of Islamization and the formation of Muslim ethnography in Indonesia and Malaysia through library research using thematic and comparative analysis. The study reveals that the maritime and cosmopolitan character of the archipelago gave rise to diverse theories of Islamic origins that ultimately strengthened cultural integration. The process of syncretism manifests at multiple levels, from ritual practices such as kenduri and maulid traditions to epistemological developments through the creation of hybrid writing systems like Jawi and Pegon scripts. Islamic educational institutions, particularly pesantren and pondok, serve as vehicles of institutional syncretism that adapt local structures while preserving core Islamic teachings, with ulama acting as cultural brokers bridging universal Islamic traditions and local realities. Sufi networks, especially the Naqsyabandiyyah Khalidiyyah Order, formed spiritual diasporas transcending modern geopolitical boundaries. In the modern era, this common cultural sphere persists through contemporary Islamic movements and intellectual exchanges. The study concludes that Indonesian-Malaysian Muslim ethnography represents a creative synthesis that maintains cultural cohesiveness despite differentiation due to colonial influences and respective socio-political contexts.